Proposed method for inspection in spray hydropneumatic - Ruas, Renato Adriane Alves; Sichoki, Diego; Dezordi, Luciel Rauni; Filho, Alberto Carvalho; God, Pedro Ivo Vieira Good (Coffee Science - ISSN 1984-3909, 2015)
The hydropneumatic sprayers transform the slurry into droplets by passing liquid under pressure through pressure nozzles. Following a strong current of air, drops splits again and carries up targets. There are few studies on inspection of these machines, especially the complexity of its operation. Thus, the objective was to propose simple and practical methodology for collecting data relating to the inspection of hydropneumatic sprayers. The proposed methodology was tested in thirty hydropneumatic sprayers used in the coffee plantations in the Alto Paranaíba – MG region. There was spray volume and index properties used in employing the method the volume of vegetation. There was also the volume of air produced by the fan sprayers in order to observe whether it was consistent with the value specified by the manufacturer. Constructed a vertical structure 3 m high to collect the pulverized in order to determine the volumetric distribution uniformity along the liquid sprayed plants. We used the chi square (χ2) to verify the adequacy of the sprayed vegetation volume. The average spray volume (581 L ha-1) was rated as medium. However, the index of average volume (59 L 1000-3) was considered high. The spray volumes need to be adjusted according to the different parts of the sprayed plants. It was concluded that the proposed methodology is feasible for the evaluation of hydropneumatic sprayers.